(untitled) (Bangladesh Journal of Botany, 2020)
A wide spectrum of chlorophyll mutants was obtained in M2 generation following mutagenesis with MMS, HZ and SA. All these chlorophyll deficient mutants were lethal except maculata, viridis and virescent. MMS treatments induced the highest frequency of chlorophyll mutations followed by HZ and SA. The frequency of chlorophyll mutations was dose dependent and increased with increasing concentrations of all the three mutagens utilized. Chlorina followed by xantha outnumbered the other types of chlorophyll mutants with all the three mutagens. Based on effectiveness, the order of mutagens was HZ > SA > MMS. Two criteria viz., pollen sterility (Mp/S) and seedling injury (Mp/I) were taken into consideration to determine the efficiency of the mutagens. With regard to these criteria, MMS mutagen was found to be the most efficient followed by HZ and SA. Lower concentrations of all the three mutagens were most effective and efficient in inducing chlorophyll mutations.